Molecular mechanism of polyunsaturated fatty acids improving spatial learning and memory in developmental rat - WANG,Li-Mei (2022)
Abstract Study on the effects and mechanisms of different oils on spatial learning and memory in developing rats. Fifty-six Sprague Dawley (SD) rats with primary weaning were randomly divided into the 7 groups, DHA, walnut oil, perilla oil, safflower seed oil, α-linoleic acid, and Essential fatty acid (EFA)-deficient and negative control. Morris water maze behavioral test was performed after 8 weeks of continuous feeding. Real-time fluorescence quantification and immunoblotting were performed to evaluate changes in the expression of NR1, CREB and c-Fos in rat hippocampus, qPCR detected the expression in hippocampal cells. The results showed that the rats fed various oils significant improvement in the Morris water maze test. The mRNA expression of NR1, CREB and c-Fos in the hippocampus of rats fed with various oils were significantly up-regulated (P<0.05 and P<0.01), and CREB and c-Fos proteins expression were up-regulated (P<0.05). The expression of genes and proteins in hippocampus of EFA-deficient control was not significantly different from negative control. It is suggested that polyunsaturated fatty acids could significantly improve the learning and memory ability of rats, which may be through regulating the mRNA expression of cfos, CREB and NR1 in rat hippocampus and the synthesis of CREB and c-Fos proteins.